(untitled) (Ascendens Asia Singapore – Bestlink College of the Philippines Journal of Multidisciplinary Research, 2024)
Student-teachers are required to undergo rigorous learning experiences such as practice teaching. It provides students with a first-hand experience of becoming a true teacher. This research study explored the extent to which students practice teaching. (SPT) Fourth-year BEED Students of Bestlink College of the Philippines prepared in Classroom Management. More reliable curricula and learning experiences are needed to develop competent teachers. The development of student readiness to act with confidence, the frequent changes in the learning environment, and guarantee that graduates of teacher’s education program will become efficient teachers. Student teachers engage in teaching practice because it is an important part of education. It is also an opportunity to apply what they learn and practice the techniques of the teaching profession. Student-teachers also know the benefits of teaching practice. It is an important aspect of preparing for their teaching profession since it will provide them with skills and knowledge in classroom management. Thus, Student Practice Teaching is considered a training requirement for teachers. The researchers believed an effective teacher must always be prepared before entering the classroom. Hence, this study intends to explain. By conducting this research, the researchers could survey how the fourth-year BEED prepares for their Student Practice Teaching. The researchers utilized the descriptive qualitative method and phenomenological approach in determining the Readiness in Classroom Management in Student Practice Teaching (SPT) of fourth-year BEED in Bestlink College of the Philippines. Systematic sampling is used in determining respondents from the fourth-year level, with 50 respondents.